“How Can You Use Two Languages and Mean What You Say in Both?”: On Translating Margaret Atwood’s Poetry into Spanish - Somacarrera, Pilar (TTR, 2005)
AbstractContrary to what might be expected, a Canadian literature in Spanish translation already exists and, expectedly, Margaret Atwood is one of the most translated writers. All her novels except Life Before Man, as well as three of her collections of short stories and three of her poetry collections have been translated into Spanish. Her work has received excellent reviews in Spain which have also praised her translators. This essay focuses on my own experience translating Atwood’s poetry–her collection Power Politics (Juegos de poder, 2000)–into Spanish, in an approach which compares my own project of translation or “projet-de-traduction,” as formulated by Antoine Berman, with that of the other translations of her poetry into Spanish. Being a university teacher and a researcher in Canadian literature, and not a specialist in Translation Studies, my approach is necessarily pragmatic and not theoretical. Bearing in mind Barbara Folkart’s contention that poetry is a cognitive activity and the multiplicity of interpretations that the poems offer, in which the feminist one is prominent, I tried to produce a translation which was as close as possible to the original characteristics of Atwood’s poetry in its tone, lineation and imagistic dimension. The first steps were the stylistic analysis, which resulted in a rhetorical study of the poems, and then the review of the existing criticism about the poems. The main problems which arose during the translation were related to the political and feminist connotations of the poems. If the political context is crucial in Power Politics, the cultural background is vital in The Journals of Susanna Moodie, although it has been erased in its Spanish version (Los diarios de Susanna Moodie, 1991, by Lidia Taillefer and Álvaro García). This is not an unusual phenomenon, since translation consists in an often insurmountable paradox which is formulated in the lines by Margaret Atwood quoted in the title of this article: trying to formulate the same idea in two languages which function differently and have completely different cultural contexts.